2003
DOI: 10.1145/792704.792707
|View full text |Cite
|
Sign up to set email alerts
|

Digital music and online sharing

Abstract: Considering the similarities and unique characteristics of online file sharing and software piracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(129 citation statements)
references
References 7 publications
(16 reference statements)
10
118
0
1
Order By: Relevance
“…The findings of this study which show a significant relationship between gender and intention to pirate software are consistent with prior research by Chiang and Assane [2], Simpson, Banerjee and Simpson [10], Siponen and Vartiainen [20], Bhattacharjee, Gopal and Sanders [26], Cronan, Foltz and Jones [27], Bachmann [28], and Kwong et al [30]. Specifically, the results reveal that males are more likely to pirate than females, which would suggest that males should be targeted in any anti-piracy education campaign.…”
Section: Findings and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of this study which show a significant relationship between gender and intention to pirate software are consistent with prior research by Chiang and Assane [2], Simpson, Banerjee and Simpson [10], Siponen and Vartiainen [20], Bhattacharjee, Gopal and Sanders [26], Cronan, Foltz and Jones [27], Bachmann [28], and Kwong et al [30]. Specifically, the results reveal that males are more likely to pirate than females, which would suggest that males should be targeted in any anti-piracy education campaign.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…While Cronan, Leonard and Kreie [23] found that age was not a significant factor, Gopal and Sanders [24], Mishra, Akman and Yazici [25], Bhattacharjee, Gopal and Sanders [26] and Cronan, Foltz and Jones [27] found that younger students were more likely to pirate software than older students. In addition, Gan and Koh [16], Bachman [28], Seale, Polakowski and Schneider [29] and Kwong, Yau, Lee, Sin and Tse [30] found that age is inversely related to the amount an individual pirates software while Masrom, Ismail and Hussein [31] and Cronan and Al-Rafee [32] found a direct relationship between the age of a person and the extent to which that person may pirate.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Gopal and Sanders [53] and Sundararajan [94] focus on technology deterrence in the context of piracy. Bhattacharjee et al [15], and Bhattacharjee et al [14] study how piracy may be limited using bundling strategies along with technology protection. 6 Chellappa and Shivendu [27] suggest that implementing various global standards is a way to limit losses due to piracy across geographic regions.…”
Section: Related Digital Piracy Literaturementioning
confidence: 99%
“…The right to a backup of a digital movie on a DVD adds value to legal downloaders, but facilitates illegal secondary sales. Since different digital rights contribute differentially towards increasing the quality of legal digital goods, and towards facilitating piracy, a careful assessment of 2 Similar issues have been recognized in the context of channel conflict caused by Web-based channels for, among other businesses, online retailing (Viswanathan, 2005) and online brokerage (Konana et al, 2000). their relative contribution towards each is important.…”
Section: Introductionmentioning
confidence: 97%